TINJAUAN LITERATUR ANALISIS YURIDIS MANAJEMEN KERAHASIAAN REKAM MEDIS ELEKTRONIK - Achmad Jaelani Rusdi; R. A. Rengganis Ularan (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
This study focuses on the importance of managing the confidentiality of electronic medical records (EMR) in the digital era as part of patients' privacy rights and the responsibilities of healthcare facilities. In Indonesia, several regulations have been established to protect patient data, such as Law No. 29 of 2004 on Medical Practice, Law No. 44 of 2009 on Hospitals, and the Information and Electronic Transactions Law (ITE) No. 19 of 2016, yet implementation continues to face significant challenges. This study uses secondary data from regulations and related literature to identify obstacles and the effectiveness of EMR data protection. The findings indicate that limited technology, insufficient understanding among healthcare personnel, and low patient awareness of their data protection rights hinder optimal confidentiality safeguards. Additionally, oversight of data access within hospitals is deemed inadequate. Increased education for healthcare workers, heightened patient awareness, and strengthened security infrastructure in healthcare facilities are essential to achieving improved patient data protection.